The Population Dynamics of the Exploited White Shells (Meretrix meretrix) at the Kambu River Estuary, Southeast Sulawesi: Dinamika Populasi Kerang Tahu (Meretrix meretrix) yang Tereksploitasi di Muara Sungai Kambu Sulawesi Tenggara - Bahtiar; Muhammad Digul Jaya Pratama; Muhammad Fajar Purnama; Muhammad Nur Findra (Journal of Tropical Fisheries Management, 2022)
White shells is one of the types of shellfish that is exploited by the community around the Kambu River estuary whose population dynamics is not known certainty. This study aims to determine the population dynamics of white shells in the Kambu River estuary, Southeast Sulawesi. This research was carried out for six months from August 2021 to January 2022. white shells were collected using garok in all parts of the waters. The shell length was measured using a caliper with an accuracy of 0.05 cm. Data on population structure, growth and mortality of clams was analyzed using FiSAT II version 3,0 software. The results showed that the population structure of white shells were dominated by one size group (young adult) which were distributed. The growth parameters of white shells consisted of asymptotic length (L∞) and growth coefficient (K) were 58,91 mm and 1.1, respectively. Natural mortality (M) of white shells at an annual mean temperature of 28oC was 1,59 yr-1, while fishing mortality (F) and total mortality (Z) of white shells were 3,16 yr-1 and 4,75 yr-1, respectively. The white shells were in an overexploitation condition with an exploitation level (E) of 0,67 yr-1.